Effect of Inorganic and Organic Zinc Supplementation on Feed Intake, Blood and Seminal Plasma Mineral Profile in Crossbred Bulls - Roy, B.; Nagpaul, P. K.; Pankaj, P. K.; Mohanty, T. K. (Indian Journal of Animal Nutrition, 2017)
Eighteen Karan Fries bulls were selected from Artificial Breeding Research Centre, ICAR-National Dairy Research Institute, Karnal, Haryana, India and randomly divided into 3 groups of 6 animals each in order to study the effect of inorganic or organic forms of Zn supplementation on feed intake and concentration of Zn,Cu and Ca in various biological samples (blood plasma, semen and hair). All the animals were fed as per NRC (2001) requirements. The animals in control group (T1) were not provided any supplemental Zn while those in groups T2 and T3 were supplemented with zinc sulfate and zinc propionate (27% available Zn) at 40 ppm level,respectively. The intakes of DM and CP were similar in all the groups. The Zn intake was higher (P<0.05) in groups T2 and T3 compared to group T1. The control diet (25.74 ppm Zn) could not fulfill the specified requirement of Zn. The intakes of Cu and Ca were similar in different groups. Supplementation of Zn either in organic or inorganic form resulted in significant (P<0.05) rise in blood and seminal plasma Zn concentration,however, no significant difference was found between two different sources of Zn supplementation. The hair Zn concentration did not change significantly due to Zn supplementation. The relationship between blood plasma Zn and seminal plasma Zn was positive (P<0.01). The supplementation of organic and inorganic Zn at40 ppm level increased Zn level in the blood and seminal plasma, however, no difference was found between organic and inorganic Zn. Either form of Zn in the diet did not affect plasma Ca and Cu concentration in the crossbred bulls. Â